ANALISIS HUKUM TERHADAP KENDALA PENYALURAN DANA BANTUAN SOSIAL TUNAI (BST) KEPADA MASYARAKAT YANG TERDAMPAK COVID-19 DI INDONESIA - Indrajaya; Dea Justicia Ardha (Legalita, 2022)
The spread of the coronavirus, the cause of which has not been determined, still thought by animals to be transmitted to humans. The World Health Organization (WHO) announced this corona virus as a pandemic with the percentage of people infected. In Indonesia, this pandemic has caused people to become consumptive and do panic buying. As a result, it affects almost all Indonesian people. The President also issued Regulations. governments substitutes. laws to reduce the impact of the covid-19 pandemic that occurred. The Perppu can be a legal basis to prevent the further spread of the coronavirus, helping people affected by the coronavirus both in terms of economy and financial stability. The solution provided by the government is in the form of basic food packages,.cash social.assistance (BST).and.direct.cash assistance (BLT).